2016
DOI: 10.1080/01616412.2016.1200287
|View full text |Cite
|
Sign up to set email alerts
|

ApaI, BsmI and TaqIVDRgene polymorphisms in association with multiple sclerosis in Slovaks

Abstract: We showed for the first time that BsmI genotype BB (AA) is associated with the decreased susceptibility to MS in Slovak population. We propose the BsmI gene polymorphism to be one of the important genetic markers in evaluation of the risk of MS. However, our data suggest that VDR gene polymorphisms ApaI, BsmI and TaqI are not useful in the prediction of disease disability progression rate in MS in Slovaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…In contrast, the C allele of TaqI appeared to predispose for MS. However, these findings have not been confirmed by other Caucasian Spanish (18), southern Spanish (33), Greek (32), Canadian (28), Slovak (30), and Dutch (34) studies. They all show no differences in allelic variant frequencies between MS patients and healthy controls.…”
Section: Taqimentioning
confidence: 66%
“…In contrast, the C allele of TaqI appeared to predispose for MS. However, these findings have not been confirmed by other Caucasian Spanish (18), southern Spanish (33), Greek (32), Canadian (28), Slovak (30), and Dutch (34) studies. They all show no differences in allelic variant frequencies between MS patients and healthy controls.…”
Section: Taqimentioning
confidence: 66%
“…Most of the published work agreed with part of our data and disagreed with others, keeping in mind these variations mainly correlated to the studied population. The study published by Cierny et al on Slovaks showed an association between BsmI and MS risk, yet no association between ApaI or TaqI and MS was detected [7]. Another study conducted by a Turkish group concluded an association between FokI and MS, yet no association was detected between TaqI or ApaI and MS risk [22].…”
Section: Discussionmentioning
confidence: 98%
“…In the perspective of substantial results from experimental work, reliable epidemiological information, and encouraging clinical findings, the theory that hypovitaminosis D as one of MS risk factors has quickly gained support and can, before long, be affirmed by more broad clinical studies. Vitamin D (VD) role in MS pathogenesis was highlighted in several studies that showed decreased level of active form of VD in initial and serious phases of MS [5][6][7][8]. Genetic variations in vitamin D receptor (VDR) gene as single nucleotide polymorphisms (SNPs) might alter VD-VDR pathway causing disturbance of VD immune-regulatory functions which consequently is reflected on MS risk [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FokI (rs2228570) and TaqI (rs731236) variants, on the other hand, can be detected with this technique. The findings published in the literature are conflicting, and these variants have been related with both risk and progression of MS (Altemaimi, Alenezi, Alserri, Alroughani, & Al‐Mulla, ; Čierny et al, ; Fukazawa et al, ); other studies observe no association, however. Meta‐analyses have not solved this controversy, finding both negative (García Martín et al, ; Huang & Xie, ) and positive results (Tizaoui, Kaabachi, Hamzaoui, & Hamzaoui, ), although they do suggest that ethnicity, age, and geographic latitude may influence the associations between these variants and MS risk.…”
Section: Discussionmentioning
confidence: 99%